Influence of multipass welding on the energy of grain boundaries in nickel alloys - Беляев, Григорий Борисович; Волосатов, Иван Ростиславович; Каховский, Николай Юрьевич (Technology audit and production reserves, 2015)
The problem of crack resistance in nickel-based alloys requires an individual approach in the study for each case. Especially difficult to describe the mechanism of crack formation is the presence of welding heat. Nickel-based alloy In52 during deposition multilayer fusing tend to form ductility dip cracks (DDC) in the heat-affected zone. Taking into account all the factors affecting the process of cracking was developed a method of numerical evaluation the strength of the grain boundaries. It was calculated the cohesive energy of the multilayer fusing made by wire In 52, in the heat-affected zone, based the thermodynamics theory of grain boundaries. Scanning electron microscope, optical microinterferometer were used to evaluate the crystallographic orientation of grain boundaries and it profile after vacuum etching. It was found that with increasing misorientation angle θ the cohesive energy is decreased. Less resistant to formation DDC are high-angle grain boundaries with range misorientation inside of 45-60º and average Ecoh 3,1 J/m2. The reasons of decrease the cohesive energy in alloys In52 during multipass fusion welding is adsorption of S and O from the grains body to grain boundary. Given similar energy absorption S and O on the GB, it can be assumed that GB concentration of oxygen is 4,5-5 times higher than the sulfur. The average concentration of O and S on the surface of DDC for high angle boundaries is inside of 2,3-4,5 and 0,5-1 at. %, respectively. Determination of the cohesive energy as a criterion of the probability formation DDC, permit to evaluate crack resistance of fusing, as well as to develop technological recommendations for prevent the formation of defects in the brittleness temperature range.